CO-EVOLUTION OF THE "MAN – SOCIETY – NATURE" SYSTEM - Kleshnia, Hanna (Proceedings of the National Aviation University Series Philosophy Cultural, 2022)
to maintain the vital activity of the biocenosis, are under irreversible changes. The aim of the study is to comprehend the place of man in the classic triangle "man – society – nature" in the context of the anthropological and ecological crisis of the globalized world. The task is to substantiate the expediency of replacing the anthropocentric concept with the concept of social ecology (environmentalism). Research methods are a set of philosophical and general scientific approaches and methods of consistency, objectivity, convergence from the abstract to the concrete. The study uses an interdisciplinary synergistic methodology to understand the dynamics of selforganization in the "man – society – nature" system. Research results. The dialectical contradiction of development is in the fact that, striving for the highest possible satisfaction of needs, man creates obstacles to achieve a strategically defined goal or even threats to his very existence. The overcoming of the revealed contradictions is associated with the rejection of man’s consumer attitude to nature, the formation of the strategy of the "man – society – nature" relations, and the limit of economic (industrial) growth. In such conditions, a timely choice how to meet the needs of nature and society is a solution to the ecological crisis. Discussion. Th. Malthus pointed to the emergence of epidemics that affect the regulation of the population. The logic of the development of world civilization led to the formation of the "paradigm of human exclusivity" (O. Yanitsky). Data of the growing of a number of people and decreasing the species of animals and plants have caused a number of theories describing the origin of numerous risks (U. Beck, H. Arendt, Ch.P. Snow, and others). The alternatives to the endless consumerism having restored harmonious relations with nature, society, and oneself, were proposed by J. Baudrillard, D. Vannes, T. Naylor, J. Heath, E. Potter, and others. Under such conditions, it seems logical to change the dominant worldview anthropocentric concept. Conclusion. The modern anthropocentric ecological situation is caused by the long-term domination of the technocratic system of values. However, technocratism as a worldview and cultural paradigm has shown its inconsistency. Recognition of nature as the core of axiological space is a step caused by the realized need to preserve the human habitat in the form of a biological species. In the current situation, politics is considered to be the main tool for greening social consciousness and introducing environmentalism as the basic ideological value of a globalized society.